A Low Cost Negative Pressure Wound Therapy Based on Arduino - Fahriansyah P, Fikri; Luthfiyah, Sari; Rahmawati, Triana; Ahniar, Nur Hasanah (Indonesian Journal of Electronics, Electromedical Engineering, and Medical Informatics, 2020)
One of the causes of increasing diabetes mellitus is irregular diet, lifestyle, and exercise. This disease can cause complications, including susceptibility to infection, so that it develops into diabetic ulcers and can lead to amputations. The purpose of this study is to design a low-cost device used to treat diabetic ulcers. The contribution of this study is that the system can help remove fluid from the wound with controlled suction pressure so that it can facilitate the healing process faster. This device is called as negative pressure wound therapy (NPWT) device, which works based on negative pressure from the vacuum motor by utilizing MPXV4115VC6U and MPXV5050VC6T1 pressure sensors at a pressure limit of 0 to -350 mmHg. Arduino microcontroller was used to process the data from the sensor. Further, the process data will then be displayed on the liquid crystal display (LCD) for user communication. The MPX4115VC6U sensor produces a pressure of -55.97 mmHg when setting -50 mmHg, and the resulting output is 3.32 volts, while the MPXV5050VC6T1 sensor produces a pressure of 51.18 mmHg at a setting of 50 mmHg. The resulting output is 3.18 volts; from the above data, it can be seen that the MPX5050VC6TI sensor has a smaller error.